Mathematic Learning With Contextual Approaches In The 21st Century - Annisa, Hurriyatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The various problems faced by teachers in the 21 st century are very complex, in the other problem is teachers must understand the demands of skills in the 21 st century that are applied to students. One solution that can be used is mathematics learning using a contextual approach. This study used a qualitative approach that presents a complete design in verbal and numerical form and presents a learning that is appropriate in the 21 st century, the research methods based on the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). Data collection techniques using observation, interviews, and documentation. The results of this study offer a design of mathematics learning with a contextual approach with the following steps: (1) observing; (2) analyze; (3) solving problems; (4) communicating